High temperature corrosion - Khanna, Anand S. (World Scientific Pub., 2016)
This invaluable book reviews the state of the art of high temperature related problems pertaining to their utility, microstructure, mechanical properties, actual behavior in different environments, their protection by various kinds of coatings at high temperatures and a new concept of nanomaterials at high temperatures.